Barodesy for clay. Issue 4 (11th October 2012) - Fellin, W.; Medicus, G.; Kolymbas, D.
Abstract : Barodesy is a new hypoplastic frame for constitutive models to describe granular materials. It has already been introduced for sand, and this article adjusts barodesy for clay. Common concepts of soil mechanics, such as critical states, barotropy (i.e. the dependence of stiffness and strength on the stress level), pyknotropy (i.e. the dependence of stiffness and strength on density) and a stress–dilatancy relation can easily be included in the presented model. Despite its mathematical simplicity, barodesy is able to describe many aspects of clay behaviour. Only four material constants are required, which can be determined by means of a single consolidated undrained triaxial test.